2016
DOI: 10.3892/mmr.2016.4769
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling for patients with nonsyndromic hearing impairment directed by gene analysis

Abstract: The aim of the present study was to investigate the genetic etiology of patients with nonsyndromic hearing impairment through gene analysis, and provide accurate genetic counseling and prenatal diagnosis for deaf patients and families with deaf children. Previous molecular etiological studies have demonstrated that the most common molecular changes in Chinese patients with nonsyndromic hearing loss (NSHL) involved gap junction protein β 2, solute carrier family 26, member 4 (SLC26A4), and mitochondrial DNA 12S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Congenital hearing loss affects approximately 1–2 infants out of every 1000, with 50% of the cases resulting from genetic factors [1]. Molecular diagnosis of hearing loss can help direct the genetic counseling and clinical management of probands and their family members [2]. One of the molecular testing methods used to diagnose hearing loss is Sanger sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital hearing loss affects approximately 1–2 infants out of every 1000, with 50% of the cases resulting from genetic factors [1]. Molecular diagnosis of hearing loss can help direct the genetic counseling and clinical management of probands and their family members [2]. One of the molecular testing methods used to diagnose hearing loss is Sanger sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, hundreds of genes causing hereditary hearing loss have been identified. Most of NSHL are induced by mutations in the four genes including GJB2, SLC26A4 , mtDNA 12SrRNA and GJB3 (59). The findings provide theoretic basis for the implementing of prenatal diagnosis of deafness genes.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 50% of deafness is associated with genetic factors, of which 70% are classified into non-syndromic hearing loss (NSHL), and approximately 80% of NSHL are caused by autosomal recessive inheritance (3,4). Previous molecular etiology studies have shown that four NSHL genes including gap junction β-2 ( GJB2 , OMIM: 121011), GJB3 (OMIM: 603324), solute carrier family 26, member 4 ( SLC26A4 , OMIM: 605646) and mitochondrial deoxyribonucleic acid 12SrRNA (mtDNA 12SrRNA , OMIM: 561000) are most common (59). Therefore, mutation screening of the four genes in people provides an effective method for the diagnosis of hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Even more important is the genetic investigation in case of hearing loss occurring in an inbred family, as it increases the prevalence of recessive forms [30] . The genetic evaluation is often long and difficult and it is based on genetic tests performed in programmed stages, on the basis of clinical suspects [18,36,72,73] . The first step is always represented by a clinical genetic evaluation; therefore, in order to plan the appropriate molecular studies, auxologic parameters and family tree are registered [69] ; facial dysmorphisms and major (such as labiopalatoschisis) and minor anomalies (such as little auricle, fifth finger clinodactily, pit, tag, renal malformations, branchial arch development anomalies) are searched [18,36] .…”
Section: Diagnostic Work-up Of Moderate-severe Hearing Loss In Childrenmentioning
confidence: 99%